Credit manual for small and medium enterprises - University of the Philippines (Diliman) Institute for Small-Scale Industries; Small Enterprises Research and Development Foundation (SERDEF). (Quezon City The Institute and SERDEF, 1996)
A manual that seeks to guide small businessmen to access financing needed for business. the manual provides a primer on sources of credit, credit procedures and alternatives to credit about which, the manual provides some financing basics and information on basic procedural and documentary requirements when borrowing from a bank and other financial institutions. The manual also features a Directory of Special Lending Programs for Small Enterprises where the various special lending programs for small enterprises are listed down and described. Descriptions include acceptable types of loan applications, loanable amounts and charges, maturity and amortization schedules, fines and penalties, collateral, loan processing and monitoring activities, contracts, and a background on the institution's program and requirements.
Keywords: Financial institutions -- Philippines -- Directories; Small business -- Finance. -- Philippines; Capitalists and financiers -- Philippines -- Directories